PENINGKATAN MEMORI PADA LANJUT USIA MELALUI TERAPI GHUNNAH - Fadhilah; Andini Nur Bahri; Zata Ismah (Penamas, 2023)
The vibrations produced by reading ghunnah have a favorable influence on a person's cognitive function, specifically in the form of memory strengthening or improvement in order to prevent senile dementia. The ability of tajweed Ghunnah is thought to have a good impact on memory. Furthermore, this capacity can help to prevent senility, which is a typical problem among the elderly. The purpose of this study was to investigate the effect of ghunnah therapy on memory. The quantitative approaches utilized in this investigation were combined with a pre-post experimental design. The Reading Span Test method was used to assess respondents' memory before and after ghunnah therapy. The goal was to demonstrate that Ghunnah's intervention variable was the only one that had an effect on memory improvement. The findings revealed that respondents' memory scores improved before and after ghunnah therapy. As a result, it is possible to conclude that ghunnah therapy has a substantial association with memory.